Micro-spherical cochleate composites: method development for monodispersed cochleate system. (2nd January 2017) - Nagarsekar, Kalpa; Ashtikar, Mukul; Steiniger, Frank; Thamm, Jana; Schacher, Felix H.; Fahr, Alfred
Abstract: Cochleates have been of increasing interest in pharmaceutical research due to their extraordinary stability. However the existing techniques used in the production of cochleates still need significant improvements to achieve sufficiently monodispersed formulations. In this study, we report a simple method for the production of spherical composite microparticles (3–5 μm in diameter) made up of nanocochleates from phosphatidylserine and calcium (as binding agent). Formulations obtained from the proposed method were evaluated using electron microscopy and small angle X-ray scattering and were compared with conventional cochleate preparation techniques. In this new method, an ethanolic lipid solution and aqueous solution of a binding agent is subjected to rapid and uniform mixing with a microfluidic device. The presence of high concentration of organic solvent promotes the formation of composite microparticles made of nanocochleates. This simple methodology eliminates elaborate preparation methods, while providing a monodisperse cochleate system with analogous quality.